Diagnosis and Management of Gestational Trophoblastic Disease: 2021 Update. Issue 1 (22nd March 2023) - Ngan, H.Y.S.; Seckl, M.J.; Berkowitz, R.S.; Xiang, Y.; Golfier, F.; Sekharan, P.K.; Lurain, J.R.; Massuger, L.
Abstract : ( Int J Gynaecol Obstet . 2021;155(suppl 1):86–93) Gestational trophoblastic disease (GTD) is a premalignant disorder that derives from an abnormal placenta. Biomarker hormone human chorionic gonadotropin found in pregnancy and postpartum can help determine disease progression.